Complementary Food Supplements Increase Dietary Nutrient Adequacy and Do Not Replace Home Food Consumption in Children 6–18 Months Old in a Randomized Controlled Trial in Rural Bangladesh. Issue 9 (31st August 2018) - Campbell, Rebecca K; Hurley, Kristen M; Shamim, Abu Ahmed; Shaikh, Saijuddin; Chowdhury, Zaynah T; Mehra, Sucheta; Wu, Lee; Christian, Parul
Abstract: Background: Inadequate complementary feeding is common in low- and middle-income countries, contributing to growth deficits. Complementary food supplements (CFSs) aim to fill dietary gaps, but few CFS studies have measured nutrient intake. In a community-based, randomized CFS trial in Bangladesh, we previously reported poor dietary diversity in 6–18-mo-old participants. Objective: We investigated, in a secondary analysis in the same trial, micronutrient intake adequacy in supplemented compared with control-arm children. Methods: At age 6 mo, children were assigned to 1 y of child-feeding counseling for mothers (control) or counseling plus 1 of 4 CFS formulations. Mothers were administered quantitative past 24-h diet questionnaires for their children at ages 6, 9, 12, 15, and 18 mo. Nutrient intakes were estimated with local recipes and food composition tables assuming average age-specific breastmilk intake. Adequacy was evaluated relative to estimated average requirements or adequate intakes. Multivariate analysis of variance and generalized estimating equation (GEE) regression models estimated the effect of each CFS on nutrient adequacy. GEE models tested dietary predictors of nutrient adequacy in the control arm. Results: A total of 25, 964 dietary modules across 5 interviews were completed. Nutrient adequacy from home foods combined with assumed breastmilk intake was low. Only 5 of 16 micronutrients were adequately consumed by >60% of children at 18 mo of age. Daily CFSs did not affect energy-adjusted micronutrient intake from home foods at any follow-up age ( P  > 0.05). CFSs increased the mean adequacy ratio for all micronutrients ( P  < 0.001 at all ages), to ≥1 for 14 of 16 micronutrients at 18 mo. Dietary diversity predicted adequate iron, zinc and calcium intake at 15 mo in unsupplemented controls. Conclusions: Home foods did not meet the estimated micronutrient needs of 9–18-mo-old children in rural Bangladesh. Daily supplementation with fortified complementary foods filled many micronutrient intake gaps and did not displace home foods. Previously, CFSs were shown to also improve linear growth and reduce stunting in this cohort. Findings support the need for CFSs in similar settings to promote nutritional well being and growth. This trial was registered at clinicaltrials.gov as NCT01562379.